PENGARUH PERBANDINGAN BUBUK COKLAT DAN TEPUNG KETAN TERHADAP SIFAT KIMIA DAN SENSORI DODOL COKLAT [Effect of the Comparison of Cocoa Powder and Glutinous Rice Flour on the Chemical and Sensory Properties of Chocolate Dodol] - Fibra Nurainy; Otik Nawansih; Merry Monika Sitanggang (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
Chocolate dodol is one of food product made from cocoa beans processingtoincrease the economic value. Chocolate dodol processing technology is simple enough to be made in small scale industry (home industry). The research was purposedto obtain a formulation of glutinousriceflour andcocoapowderto getthe best physical, chemical and sensory characteristics of chocolate dodol. The research was designed in a Completely Randomized Block Design in 4 replication. The treatments had 6 levels of comparison of cocoa powder and glutinous rice flour, that were L1 (5%:95%);  L2 (10%:90%); L3 (15%:85%); L4 (20%:80%); L5 (25%:75%); L6 (30%:70%%), respectively. Data were analyzed with analysis of variant to find the treatment effects, and the data were further analyzed with Honestly Significant Difference (HSD) test on level of 5% to find the best treatment. The research showed that the best chocolate dodol was made of 25%-30% cocoa powder and 70%-75% glutinous rice flour.  The best chocolate dodol had a plastic texture, tasteand flavor of chocolate, dark brown in color, water content of 3,49%-3,86%, fat content of 2,61%-3,00%, protein content of 0,27%, ash content of  0,69% and carbohydrate content of  92,16%.